ChemInform Abstract: A Photo‐Induced C—O Bond Formation Methodology to Construct Tetrahydroxanthones. Issue 42 (14th October 2014) - Xiao, Zheming; Cai, Shujun; Shi, Yingbo; Yang, Baochao; Gao, Shuanhu
Abstract The title transformation is based on intramolecular trapping of the reactive species produced by photocatalytic activation of a C—Cl bond.